Midkine (MDK) in cancer and drug resistance: from inflammation to therapy - Berna Yıldırım; Kudret Kulak; Ayhan Bilir (Discover Oncology)
Abstract Midkine (MDK) is a heparin-binding growth factor implicated in the pathogenesis of various diseases, including cancer, chronic inflammation, and multidrug resistance (MDR). While its expression is minimal in adult tissues, it becomes markedly elevated during embryogenesis and in response to injury, infection, or hypoxia. MDK modulates inflammatory responses by recruiting immune cells and enhancing proinflammatory cytokine production. In oncogenesis, it promotes tumor proliferation, angiogenesis, epithelial-to-mesenchymal transition (EMT), and therapeutic resistance. Elevated MDK levels are frequently associated with aggressive tumor behavior and poor clinical outcomes. This review synthesizes current knowledge on MDK’s expression profiles, molecular mechanisms, and functional roles across pathological conditions. It also discusses MDK’s emerging value as a diagnostic and prognostic biomarker, and highlights recent advances in therapeutic strategies including small molecule inhibitors, RNA-based approaches, and receptor-blocking peptides. Overall, MDK represents a promising target for future personalized therapies, although further preclinical and clinical validation is warranted to confirm its translational potential.